Perbandingan Usabilitas Aplikasi Taxi Online Android (Grab-car dan Uber) Menggunakan Unified Theory of Acceptance and Use of Technology (UTAUT) - Heru Utomo; Eriq Muh. Adams Jonemaro; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Online Taxi Android (Grab-car and Uber) is an online-based online transportation service controlled with android mobile applications. The rise of the use of online taxi applications proves that consumers are accustomed to using these services everyday. This study provides a comparison of online taxpayer usability using the unifiied theory of acceptance and use of technology (UTAUT). Comparison will be obtained from four approaches on the UTAUT model. The best performance expectancy based approach is obtained by Grab-car with satisfied value, the best Effort Expectancy approach is obtained by Uber with satisfied value, the best social impact based approach is obtained by Grab-car with satisfied value, and approach based on facilitating conditions. Best earned by Grab-car with very satisfied value.